PEMBERDAYAAN MASYARAKAT DALAM BELAJAR PEDULI COVID-19 DI DESA MARINDAL II KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Jafri Haryadi; Dara Fitrah Dwi; Nurhalimah, Nurhalimah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Societies who are used to doing activities freely have changed into new rules that have never existed before. Starting from the way of learning in schools to other community activities, they must be adapted to new ways during this Covid-19 period. For this reason, activities that are able to provide or improve the quality of people's lifestyles are needed to be smart and tough to act during Covid-19. This community service was carried out in Marinda II Village. The purpose of this service was to provide understanding to the community in making activities by complying with the rules related to Covid-19, helping the community to pay more attention to and maintain cleanliness during this Covid-19 period so that people avoid this disease. The results of this service can be seen in increasing public awareness in handling Covid-19, as evidenced by increased public awareness in providing personal protective needs and always maintaining the cleanliness of their respective living environment.